Geographical Concentration of Manufacturing Industries in Java Region, Indonesia - Wahyudi, Setyo Tri (2011)
Previous studies on geographical concentration of manufacturing industry in Indonesia demonstrated that many firms were localized in major metropolitan areas as well as in a set of emerging regions. The aim of this study is to complement the findings of the previous studies by exploring whether regional specialization and industrial concentration patterns have changed during the 1998-2007 period. This study further aims to explore the driving forces of industrial concentration in Indonesia‘s manufacturing industry, particularly for Java region, using 43 three-digit manufacturing industries (SIC151 – SIC293) over the same time period. The contribution analysis, the Theil index, and the location quotient index were employed in the analysis of the location of the manufacturing industry. The Herfindahl-Hirschman and Krugman Dissimilarity indices were used to analyze the regional specialization and concentration. This study used the fixed effect regression model to analyze the relationship between the concentration of the manufacturing industry and economies of scale, wages, labor productivity, labor intensity, urbanization economies, localization economies, and export orientation. The sample of this study consisted of 42 out of 96 regencies in six provinces in Java region. It was found that the distribution of manufacturing industry in Java is geographically scattered. The Theil index shows an increasing trend implying that the disparity of the manufacturing industry within regencies has increased. The inequality between regencies shows a decreasing trend over the period of the study, implying that the manufacturing industry in Java spreads only in several regencies. The location quotient index shows an increasing trend that reveals the economy of some regencies are more dependent on manufacturing and simultaneously it shows that several new manufacturing areas have emerged in Java. Further analysis indicated that economies of scale and wages have a positive and significant effect on the concentration of manufacturing industry, whereas labor productivity, labor intensity, urbanization economies, localization economies, and export orientation have a negative impact on manufacturing concentration.